2019
DOI: 10.1021/acsapm.9b00675
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Humidity Sensor Based on Ionic Liquid–Polymer Composites

Abstract: Polymer composites comprising the ionic liquid (IL) [Bmim]­[FeCl4] and poly­(vinylidene fluoride) (PVDF) have been developed for humidity sensing applications. Different IL contents (5, 10, and 20 wt %) were incorporated into the PVDF matrix and the morphological, physical–chemical and electrical properties of the composites evaluated, together with their humidity sensitivity response. Higher IL contents (20 wt %) induce a porous morphology in the composites. Further, IL incorporation leads to the crystallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…Addressing the changes in film structure and properties in dependence of humidity conditions is of outmost importance when considering any possible application of PEO thin films as ion transporting material. 19 Therefore, in the present work we focus on the influence of the humidity on the ionic transport of PEO thin films by using a similar experimental approach but with an improved methodology providing higher sensitivity. The here-presented approach allowed us detecting the local dielectric relaxation of the PEO thin films, depending on the probe position.…”
Section: Table Of Contents Entry 1 Introductionmentioning
confidence: 99%
“…Addressing the changes in film structure and properties in dependence of humidity conditions is of outmost importance when considering any possible application of PEO thin films as ion transporting material. 19 Therefore, in the present work we focus on the influence of the humidity on the ionic transport of PEO thin films by using a similar experimental approach but with an improved methodology providing higher sensitivity. The here-presented approach allowed us detecting the local dielectric relaxation of the PEO thin films, depending on the probe position.…”
Section: Table Of Contents Entry 1 Introductionmentioning
confidence: 99%
“…Due to good cytocompatibility and C2C12 cell proliferation, these polymer composites can be widely exploited for muscle tissue engineering applications. A similar study reported the preparation of ionic liquid-polymer composites made up of poly (vinylidene fluoride) and ionic liquid, 1-butyl-3-methylimidazolium tetrachloroferrate for the development of printable humidity sensors (Figure 3) [26]. Porosity of the composites increased with the increase in ionic liquid, and optimal surface was achieved with the addition of 20 wt.% ionic liquid to the polymer.…”
Section: Ionic Liquid Assisted Approachmentioning
confidence: 78%
“…With a simple comparison between capacitive with resistive humidity sensor, the former show good linearity and greater stability at higher humidity levels. The operation mode of capacitive sensors involves the change in the dielectric constant for the used thin film as humidity sensing occurs with varying humidity levels [12,13]. The aim of this work was to increase the sensitivity for humidity by using P3HT with different metallic nanoparticles as an active material in manufacturing Al/ P3HT / metallic nanoparticles/Al.…”
Section: Abdullah and Ibrahimmentioning
confidence: 99%